Rectangular culvert scour with non-uniform sand - Akthar, Alkhaff (2014)
This study focused on the scouring processes from a rectangular culvert outlet on a non-uniform sediment sand bed under different flow conditions and tailwater depths to establish the scour dimensions and geometry. Fourteen experiments were carried out on the non-uniform sediment bed with median size (d50) of 1.803mm and associated geometric standard deviations (σg) of 2.67.This study proposed a correlation equation between the scour volume and the scouring parameters based on past researchers’ data. The proposed correlation equation is then compared with the experimental data to determine if it is in agreement with the equation.